The Effect of Interval Back Crawl Swimming to Correct Kyphosis in Teenagers - hasan ghadimi; ramin Balouchi (Sport Sciences and Health Research)
The purpose of this study was to determine the effect of interval back crawl swimming to correct kyphosis in teenagers. Training protocol consisted of back crawl swimming for 6 weeks, 3 sessions per week (totally 18 sessions). For this purpose, out of 683 high school students, 98 kyphotic students were identified and their kyphosis was measured by a flexible ruler. During the next phase, 47 subjects with experience of participating in educational swimming classes were identified. Then, back crawl swimming skill test was performed and 38 subjects with optimal skill were identified. Then, 15 subjects with the highest degree of skill were selected purposefully for the experimental group and 15 subjects were randomly selected for the control group. The mean age in the control group was 16.4+4.65, and in the experimental group was 16.2±7.42. Subjects’ average kyphotic degree in the control and experimental groups were respectively 45.83±2.18 and 46.19±3.72. Subjects’ kyphosis was measured at the beginning (pretest), in the middle (after 3 weeks of training) and at the end of training program (posttest) by the flexible ruler. Experimental group performed the training protocol for 6 weeks, 3 sessions on the second week while the control group did not perform any training protocol. Training protocol included warm-up (5 minutes) and freestyle swimming (5 minutes); then, interval back crawl swimming was performed in 5 stages (each stage 10 minutes) consisting of back crawl swimming (6 minutes) along with stretching in the water (2 minutes) with a rest interval (2 minutes). At the end of the protocol, subjects cooled down for 5 minutes. The one-way ANOVA was used to analyze the data. The results of this study indicated that back crawl swimming had a positive effect on altering and improving kyphosis in high school students (P?0.05). The results indicated that back crawl swimming significantly decreased kyphosis degree. Therefore, we concluded that this method of training can have a positive effect on improving and treating kyphosis in high school students, so coaches and trainers can use this method to alter and treat this abnormality in teenager student.